Hang a thousand trees with ribbons : the story of Phillis Wheatley - Rinaldi, Ann (Harcourt, 2005)
A fictionalized biography of the eighteenth-century African woman who, as a child, was brought to New England to be a slave, and after publishing her first poem when a teenager, gained renown throughout the colonies as an important African-American poet.